The phylogenetic position of the enigmatic Balkan Aulopyge huegelii (Teleostei: Cyprinidae) from the perspective of host-specific Dactylogyrus parasites (Monogenea), with a description of Dactylogyrus omenti n. sp - Benovics, Michal; Kičinjaová, Maria Lujza; Šimková, Andrea (Parasites & vectors, 2017)
BACKGROUND: The host specificity of fish parasites is considered a useful parasite characteristic with respect to understanding the biogeography of their fish hosts. Dactylogyrus Diesing, 1850 (Monogenea) includes common parasites of cyprinids exhibiting different degrees of host specificity, i.e. from strict specialism to generalism. The phylogenetic relationships and historical dispersions of several cyprinid lineages, including Aulopyge huegelii Heckel, 1843, are still unclear. Therefore, the aims of our study were to investigate (i) the Dactylogyrus spp. parasites of A. huegelii, and (ii) the phylogenetic relationships of Dactylogyrus spp. parasitizing A. huegelii as a possible tool for understanding the phylogenetic position of this fish species within the Cyprininae lineage. RESULTS: Two species of Dactylogyrus, D. vastator Nybelin, 1924 and D. omenti n. sp., were collected from 14 specimens of A. huegelii from the Šujica River (Bosnia and Herzegovina). While D. vastator is a typical species parasitizing Carassius spp. and Cyprinus carpio L, D. omenti n. sp. is, according to phylogenetic reconstruction, closely related to Dactylogyrus species infecting European species of Barbus and Luciobarbus. The genetic distance revealed that the sequence for D. vastator from A. huegelii is identical with that for D. vastator from Barbus plebejus Bonaparte, 1839 (Italy) and Carassius gibelio (Bloch, 1782) (Croatia). Dactylogyrus omenti n. sp. was described as a species new to science. CONCLUSIONS: Our findings support the phylogenetic position of A. huegelii within the Cyprininae lineage and suggest that A. huegelii is phylogenetically closely related to Barbus and Luciobarbus species. The morphological similarity between D. omenti n. sp. and Dactylogyrus species of Middle Eastern Barbus suggests historical contact between cyprinid species recently living in allopatry and the possible diversification of A. huegelii from a common ancestor in this area. On other hand, the genetic similarity between D. vastator ex A. huegelii and D. vastator ex C. gibelio collected in Balkan Peninsula suggests that A. huegelii was secondarily parasitized by D. vastator, originating from C. gibelio after introduction of this fish species from Asia to Europe.
Keywords: druhová specificita; Bosna a Hercegovina; Fish Diseases; Host specificity; Asia; fylogeneze; Phylogeny; Bosnia and Herzegovina; Coevolution; Croatia; infekce červy třídy Trematoda; Asie; Itálie; Phylogeography; Species Specificity; Cyprinidae; hostitelská specificita; Animals; Cyprininae; zvířata; nemoci ryb; Trematoda; fylogeografie; Chorvatsko; Trematode Infections; Italy; Aulopyge; Host Specificity; Dactylogyrus